Differences in IgG afucosylation between groups with and without carotid atherosclerosis - Cuihong Tian; Xingang Li; Hongxia Zhang; Jieyi He; Yan Zhou; Manshu Song; Peixuan Yang; Xuerui Tan (BMC Cardiovascular Disorders)
Abstract Background A previous study demonstrated that N-glycosylation profiles of IgG are associated with subclinical atherosclerosis in a British population. However, the generalisability of this finding to other ethnic groups remains to be investigated, and it has yet to account for additional traditional atherosclerotic risk factors. The present study, thus, aims to explore IgG N-glycosylation profiles in Han Chinese with atherosclerosis, and their potential role in atherosclerosis, while controlling for traditional atherosclerotic risk factors. Methods Data of this case-control study were obtained from an established umbrella Health Examination Cohort Study (registration number: ChiCTR2100048740). The investigation was conducted at the Health Care Centre of the First Affiliated Hospital of Shantou University Medical College in China, from August 1, 2021, to July 31, 2022. A sample of 69 carotid atherosclerosis (CAS) cases was recruited from the umbrella cohort, along with 69 controls without carotid atherosclerosis, matched by traditional atherosclerosis-related risk factors, including gender, age, smoking, alcohol consumption, hypertension, diabetes, dyslipidemia and obesity. Subsequently, serum IgG N-glycosylation was profiled using Ultra-Performance Liquid Chromatography. Results After propensity score matching, the relative abundance of IgG fucosylation in CAS cases was significantly lower than that in controls [95.32 (92.96, 95.99) vs. 95.96 (94.70, 96.58), P = 0.022]. The traditional atherosclerosis-related risk factors showed no statistically significant difference between CAS cases and controls (P > 0.05). Conclusions The reduced fucosylation of IgG in CAS cases underscores the pivotal role of afucosylation in CAS. Enhancing the inflammatory capability of IgG via initiating antibody-dependent cell-mediated cytotoxicity could be the potential mechanism behind this, which should be further verified by functional studies.